A two year review of indications and outcomes of obstetric admissions to ICU of a tertiary care hospital - Mashruwala, Vishrut M.; Patel, Amrita D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Managing critically ill obstetric patients presents a unique challenge. The outcomes of these cases not only serve as a measure of the quality of patient care but also aid in refining risk stratification for pregnant patients and evaluating new therapeutic approaches. This study aims to review a series of critically ill obstetric patients admitted to our ICU, examining the spectrum of diseases, necessary interventions and maternal outcomes, while identifying factors linked to maternal mortality. Methods: This retrospective observational study was conducted in 7-bed obstetric ICU in a 300 bedded tertiary care hospital over 2-year period (August 2022-July 2024) at 1200 Bed Medicity Hospital, B. J. Medical College, Ahmedabad, Gujarat, India. Results: Only obstetric patients were admitted to the ICU. The leading obstetric indication for ICU admission was hypertensive disorders (28.8%). Maternal mortality was 3.03%. The main cause of maternal death was due to medical disorders (32.7%). ICU interventions included mechanical ventilation, blood products transfusion, inotropes, anti-hypertensives and dialysis. Conclusions: The demand for ICU management of obstetric conditions is increasing. Hypertensive disorders of pregnancy and hemorrhage have been the leading reasons for obstetric ICU admissions over the past two years. To improve outcomes for mothers and babies, it is essential to involve a multidisciplinary team early, including intensivists, obstetricians and physicians, to provide coordinated care. Obstetric teams should also develop basic skills in managing high-dependency unit (HDU) cases. This study highlights the importance of screening and preventing preeclampsia, providing antenatal education and encouraging early reporting and referral of complications.